Pengaruh Gaya Kepemimpinan dan Fasilitas Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT Samantaka Batubara Kecamatan Peranap Kabupaten Indragiri Hulu - Wilky Refalina Ferli; Marta Widian Sari; Ai Elis Karlinda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The purpose of this study is to determine and examine the influence of leadership style, work facilities on employee performance with job satisfaction as an intervening variable at PT Samantaka Batuabra, Peranap District, Indragiri Hulu Regency. The data analysis method uses a questionnaire, with a sample of 40 respondents. The analysis method used is structural equation modeling (SEM) analysis using the partial least squares (SMART PLS) program. Partial least square (PLS) based on the research result shows that, (1) There is a positive and significant between Leadership Style on Job Satisfaction at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (2) There is a positive and significant influence between Work Facilities on Job Satisfaction at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (3) There is no positive and significant influence between Leadership Style on Employee Performance at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (4) There is a positive and significant influence between Work Facilities on Employee Performance at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (5) There is no positive and significant influence between Job Satisfaction on Employee Performance at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (6) Job Satisfaction does not mediate Leadership Style on Employee Performance at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency, (7) Job Satisfaction cannot mediate Facilities The Effect of Workplace Perspectives on Employee Performance at PT Samantaka Batubara, Peranap District, Indragiri Hulu Regency.